Herd characteristics influence farmers' preferences for trait improvements in Danish Red and Danish Jersey cows. (2nd July 2016) - Slagboom, M.; Kargo, M.; Edwards, D.; Sørensen, A. C.; Thomasen, J. R.; Hjortø, L.
ABSTRACT: The aim of this study was to characterize preferences of farmers for breeding goal traits with Danish Red (DR) or Danish Jersey (DJ) cows. A breed-specific survey was established to characterize farmers' preferences for improvements in 10 traits, by means of pairwise rankings using the online software 1000Minds. These pairwise rankings were based on equal economic worth of trait improvements. The DR survey was filled in by 87 farmers and the DJ survey by 76 farmers. Both DR and DJ farmers gave the highest preference to improvements in mastitis, and the lowest to calving difficulty. By means of a cluster analysis, three distinct clusters of farmers were identified per breed. Comparisons of herd characteristics between clusters suggest that farmers choose to improve traits that are problematic in their herds. This study shows that heterogeneity exists in farmers' preferences for trait improvements and that herd characteristics influence these preferences in DR and DJ.